TWEETING BETWEEN THE LINES: EXPLORING CODE MIXING IN THE TWITTERSPHERE - Daulay, Sholihatul Hamidah; Lubis, Rodiatul Audiyah (Universitas Suryakancana, 2024)
Communication is the most essential thing in purpose. In life, sometimes we communicate with people who speak different languages from ours. Moreover, it could be an obstacle to the process of communication in society. In everyday life, we often use code-mixing with the aim of making the person immediately understand what we say. Code-mixing is the practice of combining two or more languages or language varieties within a single conversation, sentence, or even word. This research aims to analyze code-mixing phenomena in the Twittersphere. This research focused on recognizing the types of code-mixing and factors influencing code-mixing by Twitter users. This study uses a descriptive qualitative research design. The subject of this study is Twitter users who post tweets that contain code-mixing. The researcher uses documentation as a data collection method. The data for identifying the types of code-mixing were collected by documentation, such as the tweets posted previously by Twitter users on the Twitter platform.